2021
DOI: 10.3389/fphar.2021.638885
|View full text |Cite
|
Sign up to set email alerts
|

G6PD Variants and Haemolytic Sensitivity to Primaquine and Other Drugs

Abstract: Restrictions on the cultivation and ingestion of fava beans were first reported as early as the fifth century BC. Not until the late 19th century were clinical descriptions of fava-induced disease reported and soon after characterised as “favism” in the early 20th century. It is now well known that favism as well as drug-induced haemolysis is caused by a deficiency of the glucose-6-phosphate dehydrogenase (G6PD) enzyme, one of the most common enzyme deficiency in humans. Interest about the interaction between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 96 publications
1
25
0
Order By: Relevance
“…The previous studies also identified G6PD Mahidol and Viangchan variants as the major variants among healthy individuals in southern Thailand [17,18]. These variants were also commonly present in neighboring countries, including Cambodia, Laos, Myanmar [23,42]. We detected a small portion of G6PD Kaiping (1,388G> A), Union (1,360C> T), and Mediterranean (563C> T).…”
Section: Discussionsupporting
confidence: 69%
“…The previous studies also identified G6PD Mahidol and Viangchan variants as the major variants among healthy individuals in southern Thailand [17,18]. These variants were also commonly present in neighboring countries, including Cambodia, Laos, Myanmar [23,42]. We detected a small portion of G6PD Kaiping (1,388G> A), Union (1,360C> T), and Mediterranean (563C> T).…”
Section: Discussionsupporting
confidence: 69%
“…All of the variants are sensitive to 8aminoquinolines, with life threatening drug-induced severe acute haemolytic anaemia occurring even in patients with socalled mild variants (Pamba et al, 2012;Monteiro et al, 2016). The clinical complexity of the event in part explains the danger of oversimplified rules of thumb regarding this serious problem (Chu and Freedman, 2019;Bancone and Chu, 2021).…”
Section: Human G6pd Deficiencymentioning
confidence: 99%
“…G6PD deficiency affects more than 400 million people worldwide [78][79][80]. A deficiency that occurs secondary to the mutation of the G6PD gene on the X chromosome was discovered in the 1950s, when American soldiers experienced acute hemolytic anemia due to antimalarial treatment; this deficiency is known as primaquine sensitivity syndrome [81,82].…”
Section: G6pd Deficiencymentioning
confidence: 99%